The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.iecr.8b03850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Support and Its Surface Modifications in Cobalt-Based Fischer–Tropsch Synthesis

Abstract: Support effects in heterogeneous catalysis are evolving as an important field of investigation to optimize catalyst properties. The cobalt-based Fischer−Tropsch (FT) catalysts usually consist of metallic cobalt nanocrystallites dispersed on a support material. The present review surveys the progress that has been made over the last couple of decades in the area of the effect of the support and its surface modifications in cobalt-based FT synthesis. Different catalyst supports such as alumina, silica, titania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 206 publications
0
52
0
Order By: Relevance
“…[24] On the other hand, the Cobased catalysts are attractive for commercial interest due to its relatively long life time and high deactivation resistance toward an oxidation by water formed during FTS besides higher activity and selectivity to long chain C 5 + hydrocarbons. [23,[25][26][27] The particle sizes and crystallographic structures of Co nanoparticles have been considered as the key parameters for achieving a good FTS activity. For example, Bezemer et al revealed that both FTS activity and C 5 + selectivity were found to be strongly dependent on the Co particle sizes in the range of 6-8 nm.…”
Section: Production Of Liquid Hydrocarbon Fuels From Syngas Via Fts Pmentioning
confidence: 99%
See 4 more Smart Citations
“…[24] On the other hand, the Cobased catalysts are attractive for commercial interest due to its relatively long life time and high deactivation resistance toward an oxidation by water formed during FTS besides higher activity and selectivity to long chain C 5 + hydrocarbons. [23,[25][26][27] The particle sizes and crystallographic structures of Co nanoparticles have been considered as the key parameters for achieving a good FTS activity. For example, Bezemer et al revealed that both FTS activity and C 5 + selectivity were found to be strongly dependent on the Co particle sizes in the range of 6-8 nm.…”
Section: Production Of Liquid Hydrocarbon Fuels From Syngas Via Fts Pmentioning
confidence: 99%
“…[30] Therefore, the selection of catalyst support is particularly noteworthy for achieving a high FTS activity with C 5 + hydrocarbon selectivity. [25] Besides the above factors, the suitable interactions between the Co species and supports, and optimal amount of Co metals on the supports are another important feature to obtain the catalytically active species. Very strong interaction would lead to the low degree of Co reduction, whereas a weak interaction would cause a poor dispersion of active Co metal.…”
Section: Production Of Liquid Hydrocarbon Fuels From Syngas Via Fts Pmentioning
confidence: 99%
See 3 more Smart Citations